Dental Age Estimation by Demirjian’s and Nolla’s Method in Children of Jorpati, Kathmandu - Khanal, Sanskriti; Acharya, Jemish; Shah, Priyanka (Journal of College of Medical Sciences-Nepal, 2018)
Background: Growing individuals not only differ in the timing of the maturational events, but also in the sequence of these events. Age is one of the essential factors, which play an important role in every aspect of life like in clinical, medico-legal, forensic and anthropological applications and in planning treatment of orthodontic and pedodontic patients. The aim of the study was to determine dental age from orthopantomogram using Demirjian’s method and Nolla’s method and to evaluate the interrelationship between chronological and dental age according to both these methods. Materials and Methods: A cross sectional study was carried out in 177 orthopantomograms of the patient aged between 5 to 15 years. Dental age estimation was done with Demirjian’s and Nolla’s method. Results: The mean chronological age 10.14 + 3.16 compared with the mean Demirjian age 9.58 + 3.39 was statistically non significant p > 0.05 whereas comparision with mean Nolla age 7.88+ 1.56 was significant statistically. Conclusions: Both methods showed delayed dental age compared to chronological age. Demirjian’s method was more applicable to assess the dental age in Nepalese children compared to Nolla’s method. Keywords: chronological age; dental age; Demirjian’s method; Nolla’s method.